Modelling atmospheric effects on performance and plume dispersal from natural draft wet cooling towers. Issue 136 (January 2015) - Chahine, A.; Matharan, P.; Wendum, D.; Musson-Genon, L.; Bresson, R.; Carissimo, B.
Abstract: The study of cooling towers in realistic atmospheric conditions is important to assess their performance and plume dispersal as a function of wind speed and hygrometric conditions for their economical and public health consequences. In the present work the plume formation and its dispersal are modeled using a finite volume method on grid including details of the towers. The air mass flow and heat transfer are simulated inside and outside the tower. The equations for the transport of momentum, mass and liquid potential temperature are solved using the CFD software Code Saturne. In contrast to other studies dealing with the performance of cooling towers, the exchange processes inside the tower are represented with a source terms approach. The adiabatic expansion of the plume at the exit of the tower in the atmosphere is accounted for using the thermodynamical laws. The results of the simulation are compared to the measurement at Bugey nuclear power plant. The results of the model are shown to be in good agreement with the field measurements from point of view of the air flow structures, plume patterns and thermodynamical variables. Based on this reference simulation we study the variation of the cooling tower performance against the wind speed and quantify the effect of the ambient wind speed increase on the reduction of the natural draft. We also discuss the sheltering effect that the upstream tower can have on the other.